The associations between cognitive ability and L2 development under five different instructional conditions. (12th April 2019) - Li, Shaofeng; Ellis, Rod; Zhu, Yan
Abstract: This study examines the effects of two cognitive abilities—language analytic ability (LAA) and working memory (WM)—on language learning under five different instructional conditions. One hundred fifty eighth-grade English as a foreign language learners underwent a 2-hr treatment session. They were divided into five groups based on whether and when they received form-focused instruction. One group received pretask instruction on the linguistic target (English passive voice) before performing two narrative tasks; a second group received within-task feedback but no pretask instruction; a third group received both pretask instruction and within-task feedback; a fourth group received feedback after completing the tasks; and the fifth group only performed the tasks. The results showed that (a) LAA was predictive of the posttest scores of the group that only performed the communicative tasks and the group who received posttask feedback, (b) WM was associated with the learning outcomes of the two groups receiving within-task feedback, and (c) neither cognitive variable was implicated in the group that received pretask instruction before performing the tasks. The results suggest that the impact of LAA is evident when there is less external assistance and that WM is involved when learners face the heavy processing burden imposed by within-task feedback.